Estimation of global karst carbon sink from 1950s to 2050s using response surface methodology - Bin Jia; Guoqing Zhou (Geo-spatial Information Science, 2024)
For the estimation of global karst carbon sink, a few conventional methods usually require the parameters that are difficult to measure, resulting in the big cost. Moreover, under the constraints of incomplete and timeliness issues in the collection of data over a large region, it has remained a challenge for these methods to study global karst carbon sink. Therefore, this paper proposes estimating the global karst carbon sink, and analyzing the suitability of the response surface methodology and the fluctuating variation of karst carbon sink in global karst regions from 1951 to 2050. This paper shows that the proposed method can reduce the time of numerical calculation and is suitable for application in global weathering models; The global karst carbon sink in the future changes not only displays an upward trend but also exposures its fluctuating trend largely. This fluctuation is probably due to global warming.